PENERAPAN METODE DRILL BERBANTUAN MULTIMEDIA UNTUK MENINGKATKAN KETERAMPILAN MELAFALKAN KOSAKATA BAHASA INGGRIS DI SMK - Riyanto, Slamet; Sutapa, Y, Gatot; Mering, Aloysius (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research was to determine the benefits of multimedia assisted drill method in learning. The lack of interest of learners to learn English became the basis of this research. This is indicated by the results of observation that are: (1) learners were less enthusiastic in accepting lessons, (2) quickly getting bored, (3) not focusing on receiving lessons, and (4) assuming that learning English is just a no meaning. This research used descriptive qualitative approach. Data collection techniques used observation, interview, and documentation. Data analysis techniques by reviewing and explaining the observations made by researchers in accordance with the observation sheet and records in the field. The results of the research were: (1) drill scenario scenario for skill of pronunciation of vocabulary in class X SMK Negeri 1 Sadaniang, (2) order of use of multimedia assisted drill method, (3) effectiveness of drill method on learning English vocabulary pronunciation. Learning English by utilizing multimedia began by determining the contents of the components contained in the design of learning. The conclusion obtained that the method of drill aid of multimedia is very helpful learners in achieving mastery learning. Keyword: Metode Drill, pronunciation skill, Multimedia